Computational intelligence in steganalysis environment - Din, Roshidi; Samsudin, Azman (2008)
This paper presents gives a consolidated view of digital media steganalysis from the perspective of computational intelligence (CI). The environment of digital media steganalysis can be divided into three (3)domains which are image steganalysis, audio steganalysis, and video steganalysis. Three (3) major methods have also been identified in the computational intelligence based on these steganalysis domains which are bayesian, neural network, and genetic algorithm. Each of these methods has pros and cons. Therefore, it depends on the steganalyst to use and choose a suitable method based on their purposes and its environment.